2018
DOI: 10.1371/journal.pone.0190132
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of global antimicrobial resistance surveillance system (GLASS) in patients with bacteremia

Abstract: The global antimicrobial resistance surveillance system (GLASS) was launched by the World Health Organization (WHO) in 2015. GLASS is a surveillance system for clinical specimens that are sent to microbiology laboratory for clinical purposes. The unique feature of GLASS is that clinical data is combined with microbiological data, and deduplication of the microbiological results is performed. The objective of the study was to determine feasibility and benefit of GLASS for surveillance of blood culture specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 11 publications
(6 reference statements)
1
65
0
Order By: Relevance
“…AMR rates in Cambodia appear to be in keeping with the limited number of reports of regional AMR rates. Surveillance of GLASS organisms in Thailand has shown high resistance rates among E. coli and K. pneumoniae to 3GC, and ciprofloxacin, with wellpreserved sensitivity to meropenem and cefepime (Sirijatuphat et al, 2018). A review of antibiotic susceptibilities in Africa and Asia also demonstrated high 3GC, co-trimoxazole, and gentamicin resistance among Asian E. coli and K. pneumoniae isolates (Ashley et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…AMR rates in Cambodia appear to be in keeping with the limited number of reports of regional AMR rates. Surveillance of GLASS organisms in Thailand has shown high resistance rates among E. coli and K. pneumoniae to 3GC, and ciprofloxacin, with wellpreserved sensitivity to meropenem and cefepime (Sirijatuphat et al, 2018). A review of antibiotic susceptibilities in Africa and Asia also demonstrated high 3GC, co-trimoxazole, and gentamicin resistance among Asian E. coli and K. pneumoniae isolates (Ashley et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Most clinically available antibiotics have become ineffective against such bacteria, thereby increasing medical expense, prolonging the duration of illness, and raising the mortality rate . GLASS encourages countries to establish surveillance standards based on national priorities and resources available . In 2017, the same organization announced a priority list of antibiotic‐resistant bacteria, with the aim of facilitating the research, discovery, and development of novel and efficient antibiotics to treat infections caused by these pathogens .…”
Section: Introductionmentioning
confidence: 99%
“…[4,[6][7][8] GLASS encourages countries to establish surveillance standards based on nationalp riorities and resources available. [9] In 2017, the same organization announced ap riority list of antibiotic-resistantb acteria, with the aim of facilitating the research, discovery,a nd developmento f novel and efficient antibiotics to treat infections caused by these pathogens. [1,5] In response to the WHO'sc allt oa ction, it is imperative to invest time and efforti nt he search foran ew generation of effective antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus ( S.aureus ) is still an important clinical pathogen, which can lead to localized infections such as skin and soft issue infection and systemic severe infections, such as septicemia and sepsis [1,2] . Since first discovered in England, methicillin-resistant S. aureus (MRSA) has quickly been a predominant epidemiological pathogen worldwide [3] .…”
Section: Introductionmentioning
confidence: 99%